RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays Saccharata Sturt) TERHADAP TAKARAN PUPUK HAYATI DAN PUPUK NPK MAJEMUK - Panani, Harris; Hawalid, Heniyati; Rosmiah, Rosmiah (Universitas Muhammadiyah Palembang, 2016)
Response Growth and Production of Sweet Corn (Zea mays saccharata Sturt) dose Mycorrhizae and Biological Fertilizer NPK Compound Fertilizer. The aim of this study was to evaluate the response of administration of Biological Fertilizer and Compound Fertilizer NPK on the growth and yield of sweet corn (Zea mays sacchrata Sturt). This research has been conducted on an experimental garden campus of the University of Muhammadiyah Palembang C, Semambu Island Village, District North Inderalaya, Ogan Ilir, South Sumatra Province. This study took place from May to July 2015. This study used a randomized block design (RAK) factorial combination with 12 treatments and 3 replicates with four plants examples. As for the treatment of the following factors: Biological Organic Fertilizer dose (H), H1 = 5g/plant, H2 = 10g/plant, H3 = 15g/plant. NPK Compound Fertilizer dose (M), M0 = Without treatment (control), M1 = 50 kg/ha (0,94g/plant), M2 = 100 kg/ha (1,9g/plant), M3 = 150 kg/ha (2.8 g/plant). The results showed that the best treatment is a biological fertilizer mycorrhizal with a dose of 10 g/plant and NPK compound fertilizer with a dose of 2.8 g/plant . The highest production on H2M3 treatment is 4.7 kg/plot (13 ton/ha).